Developing a podcast to support professional dialogue amongst colleagues working in Higher Education: A Reflective Article. (1st July 2022) - Owen, Alex
Abstract : This reflective article provides an informed analysis and insights into the creation of a podcast series to support the academic development of colleagues based in higher education. The use of professional dialogue in this context, as a method to authentically support reflection with a view to enhancing practice, is presented as a challenge to the use of generalized CPD programmes for academic development. The experience of developing the podcast series, the benefits for wider practice enhancements and the success of the initiative are discussed. A reflection on the author's own learning from leading this endeavour is also detailed.